ATTITUDE TOWARDS VACCINATION IN AGING AT ELDERLY HEALTHCARE CENTER, CHONBURI - Phuwakonkunlawut, Jidapa; Uppamarn, Pawinee; Plainak, Achirapojnicha (Srinakharinwirot University Journal of Sciences and Technology, 2022)
This research aimed to study attitudes towards Vaccination in aging at Elderly Healthcare Center during May 2020 to August 2020. The Sample groups used in this study consisted of 150 people selected by Convenience Sampling at Elderly Healthcare center. The study shows that most of the respondent are self-service, female, 61-70 years old, have marital status, graduated with a bachelor’s degree, retried government official, have the cash right, and have recommended or advice vaccination through friends. Have 1 chronic disease. It was found that the most attitude affecting vaccination in aging was complete and accurate information about vaccine injections. In aging at level 3.64, rated at a high level this was followed by confidence in the effectiveness of the vaccine, the mean of 4.32, and finally, the awareness that vaccination improved the health was statistically significant at 0.05.